2019
DOI: 10.1021/acs.jmedchem.8b01402
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Antimigratory Effects of a Novel YAP–TEAD Interaction Inhibitor Identified Using in Silico Molecular Docking

Abstract: The Hippo pathway is an important regulator of cell growth, proliferation, and migration. TEAD transcription factors, which lie at the core of the Hippo pathway, are essential for regulation of organ growth and wound repair. Dysregulation of TEAD and its regulatory cofactor Yes-associated protein (YAP) have been implicated in numerous human cancers and hyperproliferative pathological processes. Hence, the YAP–TEAD complex is a promising therapeutic target. Here, we use in silico molecular docking using Bristol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 66 publications
0
54
0
Order By: Relevance
“…Actually, the functions of YAP are dependent on TEAD at most conditions. There are several reports showing that YAP promotes cell proliferation through TEAD . Therefore, there is great possibility that the regulation of Akt by YAP is dependent on TEAD family members.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the functions of YAP are dependent on TEAD at most conditions. There are several reports showing that YAP promotes cell proliferation through TEAD . Therefore, there is great possibility that the regulation of Akt by YAP is dependent on TEAD family members.…”
Section: Discussionmentioning
confidence: 99%
“…Using similar structural analysis methods, Hit-2 ( Gibault et al, 2018 ) and small molecule compounds (CPD3.1) were identified that disrupted the YAP-TEAD interaction. In addition, Hit-2 also inhibited the YAP target gene AXL, Cyr61, and CTGF in MDA-MB-231 cells, and CPD3.1 in HeLa cells, which reduced their proliferation and migration ( Smith et al, 2019 ). Celastrol inhibited the proliferation, migration and clonal expression of the H1299 lung cancer cells and triple-negative breast cancer MDA-MB-231 cells by targeting the YAP-TEAD interactions ( Nouri et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to assess its specificity and potential for development as a long term therapeutic strategy. In light of this it is important to note that more specific alternatives to verteporfin have already been developed and tested in vitro (66).…”
Section: Targeting Yap1?mentioning
confidence: 99%